Raman spectroscopy links differentiating osteoblast matrix signatures to pro-angiogenic potential - Sharma, Aikta (Matrix Biol Plus, 2019)
Mineralization of bone is achieved by the sequential maturation of the immature amorphous calcium phase to mature hydroxyapatite (HA) and is central in the process of bone development and repair. To study normal and dysregulated mineralization in vitro, substrates are often coated with poly-l-lysine (PLL) which facilitates cell attachment. This study has used Raman spectroscopy to investigate the effect of PLL coating on osteoblast (OB) matrix composition during differentiation, with a focus on collagen specific proline and hydroxyproline and precursors of HA. Deconvolution analysis of murine derived long bone OB Raman spectra revealed collagen species were 4.01-fold higher in OBs grown on PLL. Further, an increase of 1.91-fold in immature mineral species (amorphous calcium phosphate) was coupled with a 9.32-fold reduction in mature mineral species (carbonated apatite) on PLL versus controls. These unique low mineral signatures identified in OBs were linked with reduced alkaline phosphatase enzymatic activity, reduced Alizarin Red staining and altered osteogenic gene expression. The promotion of immature mineral species and restriction of mature mineral species of OB grown on PLL were linked to increased cell viability and pro-angiogenic vascular endothelial growth factor (VEGF) production. These results demonstrate the utility of Raman spectroscopy to link distinct matrix signatures with OB maturation and VEGF release. Importantly, Raman spectroscopy could provide a label-free approach to clinically assess the angiogenic potential of bone during fracture repair or degenerative bone loss.